Air traffic management accident risk, part 1: the limits of realistic modelling - Brooker, Peter (Cranfield University, 2005)
The prime goal of the Air Traffic Management (ATM) system is to control accident risk. Some key questions are posed, including: What do design safety targets really mean and imply for risk modelling? In what circumstances can future accident risk really be modelled with sufficient precision? If risk cannot be estimated with precision, then how is safety to be assured with traffic growth and operational/technical changes? This paper endeavours to answer these questions by an analysis of the nature of accidents, causal factors and practical collision risk modelling. The main theme is how best to combine sound safety evidence and real world hazard analysis in a coherent and systematic framework.